Reinventing Maine Government: How Mainers Can Shape a Sustainable Government and a New Prosperity - Caron, Alan; Osborne, David (Maine Policy Review, 2010)
In this commentary the authors highlight the challenges Maine faces. They suggest areas where the state could spend less, based on national comparative figures. They discuss what they call the “three ticking time bombs” in the state: the aging workforce, unfunded pension liabilities, and escalating costs of healthcare, and review what they consider to be inefficient structures in government at all levels. They argue that new thinking and new approaches are needed, and make a number of recommendations for “reinventing government” in Maine.
Keywords: Maine; government spending; government structure